PENINGKATAN PERTUMBUHAN VEGETATIF TANAMAN CABAI MERAH (Capsicum annuum L.) SETELAH APLIKASI EKOENZIM DAN PENYIRAMAN SECARA BERKALA - Oktavia Cintya Firnawati; Martin Joni; Made Ria Defiani (SIMBIOSIS, 2025)
The growth of red chili plants (Capsicum annuum L.), is impacted by both environmental factors and nutrition availability. Ecoenzymes have the ability to lower global warming and meet plant nutrient needs. The research was conducted to analyze the vegetative growth of red chili plants after being given ecoenzyme treatment and gradual watering. Red chili seeds are sown for 4 weeks, then transferred to polybags. The research used a two-factor factorial randomized block design method, namely administering ecoenzymes with a concentration of 0%; 0,5%; 1%; 1,5% and watering gradually by giving water every day; twice a day; once in three days. Every combination of treatments was carried out three times. The study's findings demonstrated that, two weeks after seeding, an ecoenzyme concentration of 1,5% could provide the maximum germination capacity (90%) of any concentration. Age 12 Weeks After Planting in polybags, the maximum plant height (70,16 cm) at 0% ecoenzyme concentration and daily watering; the quantity of primary branches (10,78 branches) at 1,5% ecoenzyme concentration and daily watering. Age 16 Weeks After Planting, the largest leaf area (105,13cm2) measured using Image-J when applying an ecoenzyme concentration of 0% and watering every day (control); root length (28,33cm) in the treatment of 1,5% ecoenzyme concentration and watering every three days; The shoot dry weight was the greatest (3,29 g) and the root dry weight was the greatest (0,67 g) when the ecoenzyme concentration was 1.5% and watered every day. Treatment with an ecoenzyme concentration of 1.5% and daily watering exerts the best influence on the growth of red chili plants. Keywords: Liquid fertilizer, leaf area and image-J